2021
DOI: 10.1016/j.neuroimage.2021.118189
|View full text |Cite
|
Sign up to set email alerts
|

Integrating large-scale neuroimaging research datasets: Harmonisation of white matter hyperintensity measurements across Whitehall and UK Biobank datasets

Abstract: Highlights We harmonised measures of WMHs across two studies on healthy ageing. Specific pre-processing strategies can increase comparability across studies. Modelling of biological differences is crucial to provide calibrated measures.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…These findings are somewhat unsurprising given that the software tool for WMH measurement (BIANCA) was trained on data collected from the Siemens MRI protocol. When adequate training data are available from the GE protocol, and in older subjects where higher WMH volumes are expected, it will be important to retrain the BIANCA algorithm on both Siemens and GE data, and this may improve consistency of WMH IDPs across scanners from the different manufacturers [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…These findings are somewhat unsurprising given that the software tool for WMH measurement (BIANCA) was trained on data collected from the Siemens MRI protocol. When adequate training data are available from the GE protocol, and in older subjects where higher WMH volumes are expected, it will be important to retrain the BIANCA algorithm on both Siemens and GE data, and this may improve consistency of WMH IDPs across scanners from the different manufacturers [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…First, one major limitation is the scanner change and differences in the acquisition protocol during the follow-ups, which are known to induce measurement variability. 46 However, these differences become almost inevitable with improvements in hardware and sequence design, especially for very long follow-up studies. Second, nonparticipants were older at baseline and had a higher WMH volume compared with participants.…”
Section: Discussionmentioning
confidence: 99%
“…This semi-automatized neuroimaging method has been successfully used to quantify macrostructural brain changesin volume or densityin longitudinal and cross-sectional studies on development and disease (Ashburner and Friston 2001). Previous results demonstrated that this type of multi-center study is methodologically feasible and reliable for the assessment of local changes in tissue integrity induced by a given pathological condition (Biswal et al 2010;Bordin et al 2021). The processing pipeline was standardized for patients and healthy controls as described by Ashburner and Friston (2001).…”
Section: Methodsmentioning
confidence: 99%